Temperature effects on tunable CW Alexandrite lasers under diode end-pumping - Kerridge-Johns,WR; Damzen,MJ (Optics Express, 2018)
Diode pumped Alexandrite is a promising route to high power, efficient and inexpensive lasers with a broad (701 nm to 858 nm) gain bandwidth; however, there are challenges with its complex laser dynamics. We present an analytical model applied to experimental red diode end-pumped Alexandrite lasers, which enabled a record 54 % slope efficiency with an output power of 1.2 W. A record lowest lasing wavelength (714 nm) and record tuning range (104 nm) was obtained by optimising the crystal temperature between 8 °C and 105 °C in the vibronic mode. The properties of Alexandrite and the analytical model were examined to understand and give general rules in optimising Alexandrite lasers, along with their fundamental efficiency limits. It was found that the lowest threshold laser wavelength was not necessarily the most efficient, and that higher and lower temperatures were optimal for longer and shorter laser wavelengths, respectively. The pump excited to ground state absorption ratio was measured to decrease from 0.8 to 0.7 by changing the crystal temperature from 10 °C to 90 °C.